(untitled) (Research, Society and Development, 2022)
Aim: to research through literature review, the mechanisms involved in the establishment of root resorptions. Mediators such as interleukins, prostaglandins, nitric oxide and systemic calcium available were studied in this review. Methods: On line searches were accomplished by scrutinizing the database available from PUBMED Central, BVS/BIREME. Web of Science, Science Direct, Periodic Portal from CAPES, as well as The Cochrane Library and PROSPERO were also used. The inclusion criteria were articles that described osteoclastic activity involving the hard dental tissues (cement, dentin and enamel). The search acquired 35 articles and excluded other 30. The articles acquired ranged from 1976 up to 2017. Results: the results showed that the combination of the immunologic mediators researched above will be the determinant factors on the establishment of root resorptions. Conclusions: Prostaglandins, Interleukins as well as the systemic calcium available are some of the most important factors for the establishment of root resorptions. Their final outcome, however, depends directly on the quality of injury inflicted over the group of teeth, or single tooth, involved.